Analysis of Learning Materials For Elementary Students - Layla Kurniawati; Edi Wahyono; Efi Mulyasari (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This problem of research is learning English as foreign language for the elementary school which relate to teaching materials. This research has aim to see the form of teaching material in Elementary school English textbook grade 5 (Learning By Doing). Whenever Elementary school students can be categorized to be young learners in studying English as foreign language, so the approach of teaching should use the children learning theories and the good display of learning materials presentation in the textbook. Textbook for experienced English teacher will be source and way to get inspiration for teaching, meanwhile each single task and activity in the textbook is used as guidance for inexperienced English teacher. In this analysis, the researchers are interested in analyzing the elementary school English textbook with descriptive qualitative method and using content analysis based on the indicator of communicative English textbook and children learning principles in studying EFL. the technique for collecting the data based on worksheet, document, and checklist. The results of this study are 1). The learning materials in the textbook are discourse in the form of dialogs, stories, chants, and reading texts; 2). The second form of learning material is instruction tasks and activities (questions answer and Total Physical Response (TPR); 3. The other form of learning is instruction and the last games as form of learning materials in the textbook.